Desempenho reprodutivo com inseminação artificial em suínos com doses homospérmicas e heterospérmicas - Sávio, Daniel Borges (2011)
The use of artificial insemination (AI) with heterospermic doses (Het) in swine may benefit reproductive performance by diluting individual differences among boars. However, such practice may also mask the true reproductive potential of some individuals, which can be measured through homospermic AI (Hom). This study evaluated boar reproductive performance after AI with Hom and Het doses. Ejaculates were collected from 4 boars and combined in 10 treatments: 4 with Hom doses (boars A, B, C and D) and 6 with Het doses (AB, AC, AD, BC, BD and CD) all having concentration of 3 billion spermatozoa in 80 mL doses with equal contribution of each boar. The in vitro analyses of sperm quality were: sperm membrane, DNA and acrossome integrity; mitochondrial functionality; and in vitro oocyte penetration. Thereafter, 511 females having parities from 1 to 6 were inseminated and the farrowing rate (FR) and total litter size (TB) were recorded. Both FR (Hom = 90.5% and Hem = 89.9%), and TB (Hom = 12.4 ± 0.4 and Het = 12.7 ± 0.7) did not differ (P>0,05). Some differences were observed among treatments, such as: the maximum FR (98.0%) for treatment AC and the minimum (87.0) for boar B; and a difference of two piglets among the maximum (for the CD treatment) and the minimum observed value (for the AC treatment). The only difference observed on the in vitro evaluations (P<0.05), occurred for the in vitro oocyte penetration by sperm from boars B (56.4%) and C (29.0%). No differences were detected in reproductive performance after AI using homospermic and heterospemic doses.